A stepwise approach towards diagnostic workup in dementia using online cognitive tools. (31st December 2021) - Meester, Hanneke FM Rhodius‐; Tolonen, Antti; Van Gils, Aniek M; Koikkalainen, Juha; Barkhof, Frederik; Herukka, Sanna‐Kaisa; Hänninen, Tuomo; Ngandu, Tiia; Kivipelto, Miia; Hasselbalch, Steen Gregers; Mecocci, Patrizia; Remes, Anne; et al.
Abstract: Background: Dementia affects more and more people worldwide. Unfortunately, only half of dementia cases are well recognized. This indicates a need for both efficient and tailored tools for diagnosis. To improve the number of correctly diagnosed patients while retaining cost‐effectiveness, we study a stepwise data‐driven approach for the diagnostic workup. By using the online cognitive test tool cCOG [1] as prescreener, we aim to select the right diagnostic workup for each patient. Methods: We included 710 subjects from three memory clinic cohorts (PredictND, VPH‐DARE and Amsterdam dementia cohort) with different types of dementia and subjective cognitive decline (SCD). All patients performed a neuropsychological (NP) test battery (consisting of MMSE, RAVLT, TMT‐A and B and Animal Fluency) and had MRI of the brain. A subset of 214 subjects additionally performed cCOG. To verify results we imputed missing cCOG based on corresponding NP tests [1]. From MRI, multiple imaging biomarkers were defined [2]. We tested a stepwise diagnostic approach, starting with screening using cCOG, then if needed testing with NP test battery and MRI, using the Disease State Index (DSI) classifier [2]. At each step patients were selected for the next step based on DSI model's confidence (Figure 1). Results: The stepwise approach was as accurate as performing all tests in every patient (Table 1), but it reduced the number of tests done especially in SCD patients considerably, with NP in only 57% and MRI in 38% (Table 2). This was also reflected in reduced cost per patient in typical memory clinic population (from estimated 510 € to 238‐243 €). For dementia patients the reduction in number of tests and costs was smaller. Conclusion: This study suggest that using a stepwise approach, applying online cognitive tests as prescreening at home, can reduce the number of patient visits to clinic and costs. The results were as accurate as with the standard traditional work‐up. Online cognitive testing is therefore a promising tool to funnel the patient flow to memory clinics, also in times of social distancing. References: [1] Rhodius‐Meester, H.F.M. et al. Alzheimers Dement 2020 Aug25;12(1) [2] Bruun, M. et al. Alzheimers Dement 2018 Aug17;10.